Deconstruction of traditional bunga terung tattoo and sequence of its application on Iban males of Sarawak and Kalimantan - Sonny anak Jumpo; Mohammad Puad Bebit (Fakulti Kemanusiaan Seni dan Warisan, UMS, 2019)
Bunga Terung is a symbol synonymous with the Iban tribe of Borneo. This study is aimed to deconstruct the Bunga Terung based on Jacques Deridda’s Theory of Deconstruction and Ferdinand de Saussure’s Linguistic Unit comprising of Sign, Signified and Signifier. In Sarawak, the Bunga Terung is worn by Iban males who have attained puberty to signify entry into adulthood. There are varying practices on the sequence of application of the Bunga Terung between the Iban tribes of Sarawak and Kalimantan. An interesting observation regarding the sequence is the time the Bunga Terung is worn. In Sarawak, the Isi Ginti (fish hook) tattoo is worn first – pre-puberty, followed by the Bunga Terung, and the Pantang Rekung Leher (neck tattoo) before other tattoos for the back and the legs. In Kalimantan, the Bunga Terung is not worn if the Iban male has not gone ‘berjalai’. This study discusses two findings; the significance of the Bunga Terung; and the sequence of its application on the Iban Males of Sarawak and Kalimantan.